Coupling of active ion transport and aerobic respiratory rate in isolated renal tubules. - Balaban, R S (1980)
We report the results of studies in which the cytoplasmic coupling between Na+,K+-ATPase activity (presumably a measure of active transport) and the mitochondrial respiratory rate was investigated in a tubule suspension from the rabbit kidney cortex. Simultaneous measurements of the redox state of mitochondrial nicotinamide adenine dinucleotide (NAD) (performed fluorometrically), the cellular ATP and ADP concentrations, and the oxygen consumption rate (QO2) were made under conditions known to alter the Na+,K+-ATPase turnover. Ouabain (25 microM) caused: (i) a 54% inhibition of QO2, (ii) a net reduction of NAD, and (iii) a 30% increase in the ATP/ADP ratio. The addition of K+ (5 ?M) to K+-depleted tubules caused: (i) an initial 127% stimulation of QO2 followed by a new steady-state QO2 50% above control, (ii) an initial large oxidation of NAD followed by a new steady state more oxidized than the control level, and (iii) a 47% decrease in the cellular ATP/ADP ratio. These data indicate that the cellular ATP and ADP concentrations or the ATP/ADP ratio may be part of the coupling mechanism linking Na+,K+-ATPase turnover and the aerobic metabolic rate in kidney.